(untitled) (CIPEEX, 2025)
Commercial contracts, as fundamental tools for the development of business activities, are governed by specific principles and theories that differentiate them from civil contracts. This area of ​​contemporary business law analyzes the main theoretical and normative foundations that support commercial contracts, highlighting principles such as autonomy of will, the economic function, parity between the parties, and predictability in business relationships. The research adopts a doctrinal and analytical approach, based on national legislative frameworks and influences from comparative law. Modern theories such as the theory of unpredictability, the social function of the contract, and objective good faith are also explored, observing and investigating how these elements have been incorporated into business contractual practice. The findings of the studies demonstrate that commercial contracts, with their own legal framework, have been progressively influenced by principles of public order and social values, aiming for contractual balance and economic efficiency. It is important to understand the principles and theories applicable to commercial contracts, which are vital for the proper interpretation and drafting of these instruments, especially in a constantly changing legal landscape.